Music Therapy in Pain and Anxiety Management during Labor: A Systematic Review and Meta-Analysis - Rocio Santiváñez-Acosta; Elena de las Nieves Tapia-López; Marilina Santero (Medicina, 2020)
Background and Objective: The study of music therapy in labor is unknown. The main objective of this research was to evaluate the effectiveness of music therapy to manage pain and anxiety during labor. Materials and Methods: A search strategy was used with PubMed/MEDLINE, LILACS, Cochrane, TRIPDATABASE, and Google Scholar. The selection criteria were based on randomized clinical trials; quasi-experimental research on pain intensity and anxiety during labor was evaluated. The primary outcomes were measured by the Visual Analogue Scale (VAS). A meta-analysis of the fixed effects was performed using mean differences (MD). Twelve studies were included for the final analysis, six (778 women) of which were meta-analyzed. Results: Decreased VAS scores for pain intensity associated with music therapy were found in the latent (MD: −0.73; 95% CI −0.99; −0.48) and active (MD: −0.68; 95% CI −0.92; –0.44) phases of labor. VAS scores for anxiety decreased both in the latent (MD: −0.74; 95% CI −1.00; −0.48) and active (MD: −0.76; 95% CI −0.88; −0.64) phases. Conclusion: Music therapy seems to have beneficial effects on pain intensity and anxiety during labor, especially for women giving birth for the first time. However, the evidence is qualified as low.